2019
DOI: 10.3390/nano9020282
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Nanovector for Cancer Targeted Drug Delivery Based on Graphene Quantum Dots

Abstract: Graphene quantum dots (GQD), the new generation members of graphene-family, have shown promising applications in anticancer therapy. In this study, we report the synthesis of a fluorescent and biocompatible nanovector, based on GQD, for the targeted delivery of an anticancer drug with benzofuran structure (BFG) and bearing the targeting ligand riboflavin (RF, vitamin B2). The highly water-dispersible nanoparticles, synthesized from multi-walled carbon nanotubes (MWCNT) by prolonged acidic treatment, were linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…Graphene quantum dots (GQDs), composed of few graphene layers with a size less than 30 nm, have attracted research interest due to their unique properties, such as possessing a large surface area, low toxicity and strong and tunable photoluminescence [1][2][3][4]. With these advantageous characteristics, GQDs can be used for bioimaging [5,6], biosensing [7], photovoltaics [8,9], drug delivery [10,11] and optoelectronic devices [12,13]. Both top-down and bottom-up approaches have been developed to synthesize GQDs.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene quantum dots (GQDs), composed of few graphene layers with a size less than 30 nm, have attracted research interest due to their unique properties, such as possessing a large surface area, low toxicity and strong and tunable photoluminescence [1][2][3][4]. With these advantageous characteristics, GQDs can be used for bioimaging [5,6], biosensing [7], photovoltaics [8,9], drug delivery [10,11] and optoelectronic devices [12,13]. Both top-down and bottom-up approaches have been developed to synthesize GQDs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of different types of nanoparticles along with various macromolecules are used for drug delivery. Nanoparticles in different structures are produced depending on their configuration and utility such as nanotubes [99], nanowires [100], nanoshells [101], quantum dots [102], nanopores, nanobots [103], nanoerythrocytes [104], etc. Drugs or biomolecules are attached to the nanoparticles by adsorption, covalent attachment, or entrapment [18].…”
Section: Carrier-based Drug Delivery Systemsmentioning
confidence: 99%
“…Catalysts 2019, 9, x FOR PEER REVIEW 21 of 32 benzofuran derivatives thus obtained were of particular interest, as they showed important antitumor activity against breast cancer cell lines [106]. Moreover, very recently, we have shown that it is possible to improve the delivery of this bioactive scaffold in vitro by chemically anchoring it (through the formation of amide bond) to suitably functionalized graphene quantum dots [107].…”
Section: Combination Between Oxidative and Reductive Carbonylation Wimentioning
confidence: 99%